Health status and use of medications by adults with intellectual disability in Western Australia - Cocks, Errol; Thomson, Allyson; Thoresen, Stian; Parsons, Richard; Rosenwax, Lorna (2016)
Background: Evidence suggests that adults with intellectual disability (ID) are vulnerable to poor health outcomes. This paper describes the health status and medication use of adults with ID in Western Australia. Method: We conducted a cross-sectional survey by interview of 328 adults with ID (M age = 37 years, range: 18–82) and their families/support persons (79% proxy or joint informants). Results: Although 90% of participants reported long-term health conditions (M = 2.6, range: 0–10), including epilepsy, allergies, eczema, asthma, and mental health problems, three quarters of the participants (77%) described their health as good or very good. Younger participants (18–44 years) reported osteoporosis and stroke, conditions commonly associated with ageing, more often than the general population at those ages. Medication use was high, with 70% taking one or more medications (Mdn = 3 medications, range: 0–21). Conclusions: Many participants reported that health problems affected their daily lives, yet the majority reported good health. Long-term health conditions were common and many people used several types of medications. Participants had poorer health than the Western Australian population overall. Careful monitoring of health conditions and regular review of medications are recommended to improve health outcomes for adults with ID.